Conodonta, Trilobita, and Anthozoa near the Late Frasnian Upper Kellwasser Event of the Geipel Quarry section in Schleiz, Thuringian Mountains (Germany) - D. Weyer; R. Feist; C. Girard (Fossil Record, 2003)
New recoveries of Trilobita, Anthozoa and Conodonta from the linguiformis Zone close to the Frasnian/Famennian boundary and Immediately preceding the Upper Kellwasser Event level at Schleiz (Thuringia) are investigated. The trilobites species are Harpes neogracilis Richter & Richter, 1924, Palpebralia cf. brecciae (Richter, 1913) and Acuticryphops acuticeps (Kayser, 1889), the latter is represented by several morphs with different numbers of eye-lenses; the trend to eye-reduction is discussed. The Rugosa fauna that was nearly unknown from the psychrospheric facies worldwide, comprise six taxa of the Cyathaxoniina. The rich conodont faunas permit tracing the exact boundary between the top of the Late Palmatolepis rhenana Zone and the Palmatolepis linguiformis Zone. Im Niveau der Frasnium/Famennium-Grenze werden neue Fossilfunde der letzten Trilobita, Anthozoa und Conodonta aus der linguiformis-Zone (vor dem Oberen Kellwasser-Event) mitgeteilt. Harpes neogracilis Richter & Richter, 1924, Palpebralia cf. brecciae (Richter, 1913) und Acuticryphops acuticeps (Kayser, 1889) wurden beobachtet; bei letzterem wird an Hand verschiedener Morphen mit unterschiedlicher Linsenzahl der Trend zur Augenreduktion diskutiert. Von der Rugosa-Fauna, die weltweit aus solcher psychrosphaerischer Fazies fast unbekannt blieb, sind sechs Taxa der Cyathaxoniina skizziert. Die reichen Condonta-Faunen erlauben eine präzise Grenzziehung zwischen dem Top der Late Palmatolepis rhenana-Zone und der Palmatolepis linguiformis-Zone. doi:10.1002/mmng.20030060104